PRE-SERVICE TEACHERS’ VIEWS ON ELT METHODOLOGY LEARNING AND ITS INFLUENCE ON THEIR TPACK SELF-ESTEEM - Alfan Hariri (STKIP AL HIKMAH SURABAYA, 2025)
This study explores the perceptions of English Language Teaching (ELT) teacher candidates toward methodology courses and their influence on Technological Pedagogical Content Knowledge (TPACK) self-esteem. Grounded in qualitative inquiry, the research involved classroom observation, lesson planning analysis, teaching video projects, and semi-structured interviews with pre-service teachers. Findings reveal that exposure to a range of ELT methodologies—such as Communicative Language Teaching, Task-Based Learning, and Total Physical Response—significantly enhanced students’ enthusiasm, active participation, and reflective practice. Participants demonstrated increasing competence in integrating content, pedagogy, and technology through creative media use, interactive techniques, and collaborative learning tasks. Interview data confirmed that methodology courses helped shift student thinking from understanding what to teach to how to teach effectively. Although some reported challenges with language fluency, candidates expressed strong confidence in applying ELT approaches, attributing this growth to hands-on experiences and project-based learning. The study concludes that methodology courses, when designed with active learning principles, play a transformative role in developing TPACK self-esteem among future ELT professionals